2008
DOI: 10.2176/nmc.48.101
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Meteorological Factors and Sex in the Occurrence of Subarachnoid Hemorrhage in Japan

Abstract: The sex difference in the seasonal occurrence of subarachnoid hemorrhage (SAH) and the association of meteorological factors in Japan were analyzed in 1006 consecutive patients with SAH in Toyama, Japan from 1996 to 2000. The study investigated whether these meteorological factors could explain the seasonality of the incidence of SAH in each sex. Seasonal variation of SAH occurrence peaked in spring in men, but peaked in spring and winter in women. The difference between maximum temperature and minimum tempera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 32 publications
2
16
0
Order By: Relevance
“…Aneurysmal rupture can also occur during stressful or strenuous activities such as sexual intercourse, labor, defecation, physical exertion, or sports [55]. However, these external factors may in fact conceal the climate impact, as numerous studies indicate a higher incidence of aneurysm rupture during the winter season, as well as during daytime [56][57][58][59]. Our experience of operated aneurysms also supports this statement, as illustrated in Figure 1.…”
Section: Natural History Of Unruptured Aneurysmssupporting
confidence: 72%
“…Aneurysmal rupture can also occur during stressful or strenuous activities such as sexual intercourse, labor, defecation, physical exertion, or sports [55]. However, these external factors may in fact conceal the climate impact, as numerous studies indicate a higher incidence of aneurysm rupture during the winter season, as well as during daytime [56][57][58][59]. Our experience of operated aneurysms also supports this statement, as illustrated in Figure 1.…”
Section: Natural History Of Unruptured Aneurysmssupporting
confidence: 72%
“…Differences in peak onset of aneurysmal SAH between males and females have been reported by some [3,4,5,6], but other studies have indicated no differences in seasonal variation between males and females. A Danish study [12] on differences in seasonal variation between males and females concluded that there was ‘little difference by sex', with a peak onset in females in October and in males in November.…”
Section: Discussionmentioning
confidence: 85%
“…To date, intraday variations [1], intraweek variations [2], and intrayear variations in the incidence of aneurysmal SAH have been reported. Although seasonal variations have been observed by some authors [1,3,4,5,6], other studies have indicated no seasonal variations [7]. However, in most of these studies, methodological limitations have been identified [7].…”
Section: Introductionmentioning
confidence: 99%
“…Unlike most other types of cerebrovascular disease, SAH occurs more frequently in women than in men. Mortality rates of female SAH patients have been reported to be higher than those for men 2,3,8,9,15,16,19,23,25,32,33) . Despite the catastrophic consequence of aneurysmal SAH, very little is understood regarding their pathogenesis, and there are no reliable predictive markers for identifying risk aneurysm rupture.…”
Section: Introductionmentioning
confidence: 99%
“…The cerebral aneurysm is a prevalent acquired cerebrovascular disease that can cause a catastrophic subarachnoid hemorrhage (SAH). Mortality rates for aneurysmal SAH continue to average near 50%, with 10% of patients dying before ever reaching the hospital and approximately 20% sustaining severe disability 1,6,7,18,29,32) . Unlike most other types of cerebrovascular disease, SAH occurs more frequently in women than in men.…”
Section: Introductionmentioning
confidence: 99%